Ethnic differences in association of high body mass index with early onset of Type 1 diabetes - Arab ethnicity as case study. - Arshad M Channanath; Naser Elkum; Dalia Al-Abdulrazzaq; Jaakko Tuomilehto; Azza Shaltout; Thangavel Alphonse Thanaraj (PLoS ONE, 2017)
The "accelerator hypothesis" predicts early onset of Type 1 diabetes (T1D) in heavier children. Studies testing direction of correlation between body mass index (BMI) and age at onset of T1D in different continental populations have reported differing results-inverse, direct, and neutral. Evaluating the correlation in diverse ethnic populations is required to generalize the accelerator hypothesis.The study cohort comprised 474 Kuwaiti children of Arab ethnicity diagnosed with T1D at age 6 to 18 years during 2011-2013. Age- and sex-adjusted BMI z-scores were calculated by comparing the BMI measured at diagnosis with Kuwaiti pediatric population reference data recorded during comparable time-period. Multiple linear regression and Pearson correlation analyses were performed.BMI z-score was seen inversely associated with onset age (r,-0.28; p-value<0.001). Children with BMI z-score>0 (i.e. BMI >national average) showed a stronger correlation (r,-0.38; p-value<0.001) than those with BMI z-score<0 (r,-0.19; p-value<0.001); the former group showed significantly lower mean onset age than the latter group (9.6±2.4 versus 10.5±2.7; p-value<0.001). Observed inverse correlation was consistent with that seen in Anglo-saxon, central european, caucasian, and white children while inconsistent with that seen in Indian, New Zealander, and Australian children.The accelerator hypothesis generalizes in Arab pediatric population from Kuwait.